Expansão da cana-de-açúcar na microrregião do Vale do Rio dos Bois – Goiás - Rodrigues, Hellbia Samara Moreira de Carvalho (2014)
In Brazil the intensification of international discussions in the 21st century on the production of clean and renewable energy emphasizes the expansion of sugar cane, raw material for the production of biofuel ethanol, considered to be less polluting. The recent expansion of sugar cane in Brazil has as target area the Center - South of the Cerrado Biome, mainly in land before occupied by grain, cotton and pastures and comes inducing accelerated change of land use, worrying about, among other aspects, by the environmental impacts related. Since the late 1990, especially after 2000, the cane has been expanding rapidly on areas before cultivated areas with other cultures, especially grains, in addition to pastures and increasing the number of plants. The mesoregion south of the state of Goiás, preferred for this rapid expansion of current, especially the sugar cane microregions of Quirinópolis, Southwest, of Vale do Rio dos Bois (MRVRB), is cultivates cane since the decade of 1970, when it was favored by Proálcool - Program of Alcohol, public policy federal that stimulated the production of vehicles powered by alcohol and which ran from 1975 to 1979; a new and recent expansion of cane was initiated in mid 2004. The research aims to assess the expansion of the monoculture of sugar cane in MRVRB 1985 to 2013, in order to clarify the causes of the recent process and assess its direct and indirect impacts, with emphasis in the areas of permanent preservation. The methodology was based on the interpretation of satellite images in the years 1985, 1995, 2005, 2010 and 2013, and in the interpretation of maps the physical environment through integrated analysis that have led to the drafting of the maps of suitability agricultural and the identification of areas with restrictions to the cultivation of sugar cane. It is concluded that in the period considered the standard MRVRB I have recent replacement of areas of grain and subsequently pastures besides remaining areas of Cerrado, considered to be Areas of Permanent Preservation (APP), albeit at a lower proportion. The lower expansion was assigned to the edaphic limitations and relief (topography), which together and associated to offer logistics, explain its leadership not in recent expansion of the sugarcane plantation.